In 2016, around one-third of people in Germany donated for refugees and ten percent helped out on site: Yet concerns are mounting - Jannes Jacobsen; Philipp Eisnecker; Jürgen Schupp (DIW Economic Bulletin, 2017)
The presence of refugees in Germany and the challenges their integration poses have preoccupied the public for the past two years. According to the latest data of the Socio-Economic Panel (SOEP), many more people in Germany were concerned about migration and xenophobia last year than in 2013. The additional representative results of the Barometer of Public Opinion on Refugees in Germany in 2016 and the current SOEP wave also indicated that respondents see more risks than opportunities in the refugee migration to Germany. At the same time, around one-third of the population said they had actively supported refugees in the form of monetary or material donations; around ten percent had helped out on site, for example by accompanying refugees to appointments at authorities or language instruction. People with a higher level of formal education and a history of volunteering were more likely to assist actively on site in the integration of refugees. In the course of the year, however, the number of respondents who expressed their intention to become active in the future decreased.
Keywords: A13; D64; I31; 330; Refugee; Public Opinion; Civil Engagement